Landscapes of disease : malaria in modern Greece - Gardikas, Katerina (CEU Press studies in the history of medicine, 2018)
Malaria existed in Greece since prehistoric times. Its prevalence fluctuated depending on climatic, socioeconomic and political changes. The book focuses on the factors that contributed to the spreading of the disease in the years between independent statehood in 1830 and the elimination of malaria in the 1970s. In fact, by the nineteenth century, Greece was the most malarious country in Europe and the one most heavily infected with its lethal form, falciparum malaria. Owing to pressures on the environment from economic development, agrarian colonisation and heightened mobility, the situation.